Melt spinnability of long chain cellulose esters. Issue 48 (17th June 2020) - Willberg‐Keyriläinen, Pia; Rokkonen, Teijo; Malm, Tero; Harlin, Ali; Ropponen, Jarmo
Abstract: Technical and hygienic nonwovens, originating typically from fossil‐based synthetic polymers, are the fastest growing applications in the textile industry. Recently developed thermoplastic cellulose fatty acid esters have polyolefin like rheology properties and therefore the suitability of these cellulose esters for fiber production was evaluated. In this study, the melt spinning of textile fibers has been demonstrated using thermoplastic cellulose octanoate. The mechanical properties of melt spun fibers were analyzed by using tensile testing and both the surface and cross‐section morphology of melt spun fibers were studied using the scanning electron microscopy. The surfaces of the fibers were very smooth and also the cross‐section was very uniform and no porosity was observed. While mechanical properties of the produced fibers are not yet as good as those reported for commercial polypropylene (PP) monofilament fibers, they are somewhat more comparable to other cellulose ester‐based fibers. The melt spinning results indicate that the novel cellulose‐based fibers can provide a renewable and recyclable alternative, for example, spun‐laid PP in several hygienic textile and fully oriented in technical applications in future. Abstract :